Obstacles and facilitators of parents’ coping with hematopoietic stem cell transplantation of a child with cancer - Batool Pouraboli; Maryam Maleki; Nahid Dehghan Nayeri; Amir Ali Hamidieh; Abbas Mardani (PLoS ONE, 2025)
Background Pediatric hematopoietic stem cell transplantation (HSCT) is a complex process that impacts the entire family. The traumatic nature of the pediatric HSCT period makes this a particularly vulnerable time for parents, leading to coping challenges. This study aimed to explore parents’ experiences regarding the obstacles and facilitators of coping with their child’s HSCT. Methods This qualitative study used a conventional content analysis method. The study took place at largest Children’s Medical Center in Iran from February to November 2023. The study utilized purposive sampling for selecting participants. Data collection began with unstructured interviews, followed by in-depth semi-structured interviews with open-ended questions. Sampling continued until data saturation was achieved after examining qualitative data from 20 participants. Results The qualitative analysis identified eight subcategories grouped into two main categories: “variable support” and “beliefs and individual situation”. Support varied widely, with significant roles played by family, friends, healthcare providers, non-governmental organizations, and desirable beliefs and individual situation. However, inadequate family support, financial stress, and conflicts with healthcare teams were notable barriers. Conclusions The findings underscore the need for comprehensive support systems and targeted interventions to address the emotional and practical challenges families face during their child’s HSCT vulnerable period. Future efforts should focus on enhancing support structures and addressing barriers to improve the overall coping experience for parents.